Membraneless ethanol,O2 enzymatic biofuel cell based on laccase and ADH/NAD+ bioelectrodes - Fenga, Paula Gonçalves; Cardoso, Franciane Pinheiro; Nikolaou, Sofia; de Andrade, Adalgisa Rodrigues (Eclética Química, 2019)
This work describes EtOH,O2 membraneless enzymatic biofuel cells (EtOH,O2 MlessEBFCs) that employ laccase-based biocathodes and ADH/NAD+ bioanode. Laccase biocathodes were prepared by immobilizing a polypyrrole film containing different redox mediators (ruthenium and osmium complexes). The bioanode for EtOH,O2 MlessEBFCs was fabricated by immobilizing multiwalled carbon nanotubes, NAD+-dependent alcohol dehydrogenase enzyme (ADH), poly-methylene green, and poly(amidoamine) (PAMAM) dendrimer onto a carbon cloth platform. Maximum power density and current density were 21.0 ± 0.2 mW cm-2 and 0.15 ± 0.07 mA cm-2, respectively, in PBS (pH 6.5). Lifetime tests conducted for EtOH,O2 MlessEBFCs showed promising perspectives for their future application in miniaturized devices.